Haydn's Visits to England - Hogwood, Christopher 1941-2014 (London Folio Society, 1980)
The year 1790 brought the death of Haydn's patron Nicolaus Esterházy and the subsequent sacking of his music staff; the impresario Johann Peter Salomon seized this moment to lure the celebrity composer to London for two visits in 1791 and 1794. Hogwood makes extensive use of contemporary documents such as newspaper reports and Haydn's own notebooks and letters to examine the English public's Haydn-mania and the composer's own reactions to new people and experiences.
Companion to the LP "Haydn's Music for England" (20132375; REC 12 HOGW 1980)
Keywords: Haydn, Joseph -- 1732-1809; 18th Century (1701-1800); Music history; United Kingdom